A third order nonlinear model to study the dynamic behaviour of composite laminated structures under thermal effect with experimental verification. (15th March 2019) - Sit, Moumita; Ray, Chaitali
Abstract: The present article includes the modal analysis of laminated composite structures under thermal effect. Experiments are conducted to study the influence of temperature change on natural frequencies of glass fibre reinforced polymer (GFRP) composites. GFRP laminated plates are prepared in the laboratory using vacuum bagging by resin infusion. The specimens are thermally conditioned to obtain temperature variation ranging from −10 °C to 120 °C. A Green–Lagrange nonlinear finite element (FE) model based on third order shear deformation theory (TSDT) has been developed for the analysis. The FE solutions in terms of natural frequencies are compared with experimental data and an extensive parametric study is carried out. The free vibration modal analysis of a hollow stiffened laminated panel is also carried out to identify the effect of temperature change with proper temperature distribution within the stiffened structures using 1D heat conduction model and the solutions may be used as benchmark.